Europe's Erased: Rethinking European Migration and Citizenship Policies Based on the Example of the Erased Residents of Slovenia. Issue 2 (1st June 2020) - Protner, Beja
Abstract: The erasure of more than 25, 000 people from the population registry of the Republic of Slovenia in 1992 left these people who had been living there for several years, some for all their lives, without any legal status. As such, these previously ordinary citizens became the legal equivalent of undocumented migrants. They were the first in Slovenia to experience European migration policies with their classification order of legal statuses and citizenships, which organizes populations into hierarchies both within and among the states. Their struggle to gain legal status is proof of the absurdity of these policies where desubjectivated migrants are trapped in an administrative circle that prevents their inclusion in society. Citizenship, a status that promises full participation in the community, is very hard to acquire because the community is defined as a national community. Behind the curtain of the "home security" discourse, the real goal of selective and partial inclusion of migrants seems to be protection of capital, since undocumented workers (among them also the erased residents) are unprotected from exploitation and as such are a benefit to the economy. The main argument of the article, supported by the ethnographic data, is that migration restrictions not only cause a great deal of suffering to migrants but also (re)produce their illegality. Due to the migration policies, these migrants stay in a specific territory illegally and as a consequence they cannot work in the legal sector. In order to break this vicious cycle, the official concept of citizenship has to be changed and the foundations upon which migration policies rest have to be reconstructed in the spirit of inclusiveness.